2011
DOI: 10.1111/j.1399-3054.2011.01447.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of FLC, SOC1 and FT homologs in Eustoma grandiflorum: effects of vernalization and post‐vernalization conditions on flowering and gene expression

Abstract: A rosette plant of Eustoma grandiflorum requires vernalization (exposure to a period of cold temperature) and long-day conditions to promote flowering, while prolonged cold or cool temperatures in post-vernalization periods delay flowering. This study aimed to investigate the effect of growth conditions on flowering regulation in Eustoma. In Arabidopsis, vernalization suppresses a floral repressor gene, FLOWERING LOCUS C (FLC) and upregulates floral promoter genes, such as SUPPRESSOR OF OVEREXPRESSION OF CONST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Furthermore, although FLC/MAF -like genes are found in other core eudicots, gene expression tends to be positively rather than negatively regulated by cold. This is the case for Arabidopsis MAF5 , the Texas bluebell ( Eustoma grandiflorum , Gentianaceae) EgFLCL , and trifoliate orange ( Poncirus trifoliate , Rutaceae) PtFLC (Zhang et al, 2009; Nakano et al, 2011). In A. thaliana , natural variation in vernalization responsiveness has been linked to variation in the promoter, first exon, and first intron of FLC , and within the positive regulator of FLC , FRIGIDA ( FRI ; Michaels and Amasino, 1999, 2001; El-Din El-Assal et al, 2001; Werner et al, 2005; Balasubramanian et al, 2006; Angel et al, 2011; Bond et al, 2011; Coustham et al, 2012; Wollenberg and Amasino, 2012).…”
Section: Vernalization Responsivenessmentioning
confidence: 92%
“…Furthermore, although FLC/MAF -like genes are found in other core eudicots, gene expression tends to be positively rather than negatively regulated by cold. This is the case for Arabidopsis MAF5 , the Texas bluebell ( Eustoma grandiflorum , Gentianaceae) EgFLCL , and trifoliate orange ( Poncirus trifoliate , Rutaceae) PtFLC (Zhang et al, 2009; Nakano et al, 2011). In A. thaliana , natural variation in vernalization responsiveness has been linked to variation in the promoter, first exon, and first intron of FLC , and within the positive regulator of FLC , FRIGIDA ( FRI ; Michaels and Amasino, 1999, 2001; El-Din El-Assal et al, 2001; Werner et al, 2005; Balasubramanian et al, 2006; Angel et al, 2011; Bond et al, 2011; Coustham et al, 2012; Wollenberg and Amasino, 2012).…”
Section: Vernalization Responsivenessmentioning
confidence: 92%
“…A 903 bp fragment of the GUS gene (AAC53706) was amplified with a primer set (5'-CGATGCGGTCACTCATTACG-3' and 5'-CTGTAAGTGCGCTTGCTGAG-3'). ACTIN gene was amplified as described previously (Nakano et al 2011), as a positive control of DNA extraction.…”
Section: Genomic Pcrmentioning
confidence: 99%
“…However, there are some problems, such as heat-induced rosetting (Ohkawa et al 1991), reduced rate of flowering under low temperature (Nakano et al 2011), and flower bud necrosis under low light intensity (Ushio and Fukuta 2010), which reduce the productivity of Eustoma. To study the growth and flowering habits of Eustoma by introducing a gene of interest, it is important to develop an efficient transformation method.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GhSOC1-overexpressing transgenic cotton plants were dwarfed and exhibited many more petal layers than did normal control flower buds. Overexpression of some SOC1-like genes in Arabidopsis always lead to early flowering and abnormal organ development, whereas overexpression of other genes represses flowering and disturbs the development of floral organs [59][60][61]. The expression patterns observed for flowering-related genes of Arabidopsis and upland cotton demonstrated that GhSOC1 could promote flowering and alter floral organs by up-regulating the expression of FT, SOC1 and AP1.…”
Section: Discussionmentioning
confidence: 99%